INTEGRATIVE PEDAGOGICAL STRATEGIES FOR DEVELOPING DIAGNOSTIC COMPETENCE IN MEDICAL EDUCATION: A STUDY AMONG MEDICAL STUDENTS (Scientific journal of the Fergana State University, 2026)
This study examined the theoretical and methodological foundations for developing diagnostic competence among 450 medical students studying ophthalmology. A blended teaching model combining lectures, case-based learning, and simulation significantly improved diagnostic accuracy, clinical reasoning, and self-confidence. Post-intervention assessments showed a 23.9% improvement, with simulation, feedback, and active participation as key predictors (adjusted R² = 0.63). The findings emphasize the importance of integrating simulation and AI-enhanced educational tools to cultivate analytical and diagnostic skills in future clinicians.